Cheap thrills [videorecording (DVD)] - Haaga, Trent; Chirchirillo, David; Paxton, Sara; Embry, Ethan, 1978-; Healy, Pat, 1971-; Koechner, David, 1962- (Drafthouse Films (Series), 2014)
A recently fired father facing eviction agrees to take on an escalating series of insane challenges in exchange for cash payments from a rich couple with a twisted sense of humor.